Effects of core stability exercises, lumbar lordosis and low-back pain: A systematic review - Skundric, G.; Vukicevic, V.; Lukic, N. (Journal of Anthropology of Sport and Physical Education, 2021)
Core stability has a very positive effect on the prevention of lumbar lordosis and lower back pain. The main focus of this paper was on a review of the available literature on the influence of trunk stability on lower back pain and lumbar lordosis. The two electronic databases researched for collecting articles are PubMed and ScienceDirect. A search was conducted by title, taking a predefined combination of the following keywords into account: low back pain, core stability, training, sports. Screening processes are summarized through a PRISMA flow chart. 408 studies were identified, of which 20 met the inclusion criteria. It was concluded that exercise on the stability of the pelvic nucleus and muscles is recommended as the simplest and most favorable prevention of lower back pain and lumbar lordosis. The stability of the nucleus helps to overcome the main causes and deprive the body of functional disorders and pain.